HIGH-PROFICIENCY AND LOW-PROFICIENCY LEARNERS’ COMPENSATION STRATEGIES USE IN ENGLISH LANGUAGE LEARNING - Tahmina, Tania (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Compensation strategies are vital for foreign language learners to overcome difficulties in acquiring a second language. According to Oxford (1990), these strategies help learners “overcome knowledge limitations in all four skills” (p. 90), making them essential for effective language acquisition. This study investigates the preferred compensation strategies of high- and low-proficiency English learners at Jagannath University, Dhaka, Bangladesh, using a mixed-methods approach. Data collection involved the Strategy Inventory for Language Learning (SILL) questionnaire designed by Oxford, alongside semi-structured interviews to enrich the qualitative findings. Results indicate distinct preferences based on proficiency levels: high-proficiency learners frequently employed Strategy 6: “If I can’t think of an SL word, I use a word or phrase that means the same thing” (40%). Meanwhile, low-proficiency learners favored Strategy 1: “To understand unfamiliar SL words, I make guesses” (66.66%). These findings highlight the significance of adapting teaching approaches to address diverse learner needs, ultimately enhancing language learning efficiency and effectiveness.